(untitled) (International journal of medical sciences, 2025)
This article presents evidence-based information on the etiology, clinical manifestations and modern treatment strategies of streptoderma. The relevance of the topic is determined by the growing prevalence of skin infections caused by streptococcal microorganisms among children and adults, which is associated with decreased local immunity, poor hygiene practices and environmental factors. The study analyzes the effectiveness of topical antiseptic agents, antibacterial medications, anti-inflammatory therapy, the use of probiotics and herbal-based alternative treatments. In addition, the article evaluates treatment stages, safety considerations and preventive measures according to modern dermatological guidelines. The findings highlight the importance of an individualized approach in patients with streptoderma and contribute to improving treatment quality.